KEPEMIMPINAN TRANSFORMASIONAL SEBAGAI SALAH SATU KAPASITAS DALAM BERWIRAUSAHA (ENTREPRENEURIAL CAPACITY) - Yasinta Indrianti (Pascasarjana Universitas Halu Oleo, 2020)
The implementation and practice of entrepreneurship in Indonesia to achieve success is supported by various aspects including the entrepreneurial capacity itself. In an effort to develop the concept of entrepreneurial capacity, one of the most important internal factors to be studied as preliminary research is the transformational leadership style that business actors have as an adaptive and flexible leadership style in accordance with the current entrepreneurial context. This study aims to further examine how transformational leadership is described as an important aspect of a person's entrepreneurial capacity. This research used descriptive quantitative method with convenience sample technique. Research respondents were 126 respondents. The results showed that transformational leadership style is a leadership style that is very suitable to be applied in today's entrepreneurial practice with 3 (three) main dimensions that make up transformational leadership styles, namely idealized influence, inspirational motivation, and individualized consideration.